EFFECTS OF SILAGE EFFLUENT, UREA-MOLASSES AND WATER TREATMENT ON IN SITU RUMEN DEGRADATION AND MICROBIOLOGICAL TRAITS OF WHEAT STRAW - H. G. Qutab-ud-din; M. Macit (Journal of Animal and Plant Sciences, 2020)
This experiment was carried out to determine the effects of silage effluent, urea-molasses and water treatment on in situ disappearance of dry matter (DM), organic matter (OM), crude protein (CP), acid detergent fiber (ADF), and neutral detergent fiber (NDF) of wheat straw, and its degradation parameters (a + b + c and a+b) and effective degradability (ED). There were six treatments: including control (W), W+ silage effluent (WS), W+ silage effluent + water + urea + molasses (WSHUM), W+ urea + molasses + water (WUMH), W+ urea + molasses (WUM) and W+ water (WH). Except control and WH groups, all other groups were set iso-caloric and iso-nitrogenous and calculated amount of urea and molasses equal to nitrogen and energy value from silage effluent were added to treatment groups. All treatment groups were packed in sealed plastic bucket made by polypropylene, and they were subjected to 45 days of anaerobic fermentation. Four rumen cannulated Holstein bulls of 400 kg and 20 months of age were utilized. The extent and rate of DM, OM, CP, ADF and NDF disappearance was determined by using randomized block design where animals were blocking factor. After fermentation, all treatments were incubated to rumen for 4, 8, 16, 24, 48, 72 and 96 h using nylon bag technique. Data of in situ DM, OM, CP, ADF and NDF degradability were subjected to one-way ANOVA using the GLM procedure. A completely randomized design was used in which treatment groups were the fixed factor. Differences in terms of DM, OM, CP, ADF and NDF degradabilities among the treatments were significant (p≤0.05). Treatment with silage effluent increased rumen degradability of wheat straw (p≤0.05). Also, treating wheat straw with silage effluent hindered the growth of pathogenic microorganisms. In conclusion, treating low quality roughages i.e. wheat straw with silage effluent which is rich in nutrient could be recommended not only to improve fermentation quality of wheat straw but also to increase its degradation in rumen.  Further, addition of silage effluent can preserve the ensilage from undesired pathogen i.e. yeast, coliform, clostridia and fungal growth.
Keywords: in situ degradability; ADF; NDF; Silage effluent; Wheat straw